Relationships between fungal diversity and fruit quality of Yuluxiang pear during low temperature storage - Hou, Yaru; Zhang, Xiaoyu; Gao, Zhenfeng; Chen, Tian; Zhang, Lixin (Frontiers in Microbiology, 2023)
Postharvest decay is an urgent problem that affects the storage of pears. Low temperature storage is one of the most important methods to reduce the prevalence of fruit diseases during storage. In this study, the microbial diversity of postharvest Yuluxiang pear (Pyrus × michauxii 'Yu Lu Xiang') fruits stored at low temperature for different lengths of times was analyzed. Illumina MiSeq high-throughput sequencing was used to analyze the composition and diversity of fungal communities. The results showed that the fungi within fruit were classified into 204 non-repetitive operational taxonomic units (OTUs) based on the 97% sequence similarity level. They belonged to 6 phyla, 18 classes, 40 orders, 72 families, and 92 genera. The highest richness of fungi was obtained after 30 d of treatment. The β-diversity index showed that the fungal community composition of these fruit was significantly different at the beginning of storage compared with the different timepoints of samples at low temperature during storage. The comparison of fungal composition at the phylum level indicated that Ascomycota was dominant in the different timepoints of samples at low temperature, while Alternaria was the primary fungus at the genus level. A correlation analysis was used to further explore the correlation between fungi and fruit firmness, titratable acid, and solid soluble contents at low temperatures during storage. Aureobasidium and Didymella positively correlated with the soluble solids and hardness. Phoma positively correlated with the titratable acid, and Aspergillus positively correlated with titratable acid and hardness. This study can guide the industrial production of Yulu pear and also provide a theoretical basis to prevent and control diseases during the storage period of Yulu pear.